2008
DOI: 10.3171/jns/2008/109/12/s27
|View full text |Cite
|
Sign up to set email alerts
|

Gamma Knife surgery used as primary and repeated treatment for idiopathic trigeminal neuralgia

Abstract: Object The purpose of this study was to assess the outcome of idiopathic trigeminal neuralgia (TN) treated with Gamma Knife surgery (GKS) as a primary and repeated treatment modality with a mean follow-up of 5.7 years. Methods Between July 1999 and September 2005, a total of 89 patients with idiopathic TN underwent GKS as a primary treatment. The entry zone of the TN was targeted with a 4-mm collimator and treated with a maximal dose of 60–90 Gy (mean 79 Gy). The dose to the pontine margin was always kept <… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
18
0

Year Published

2010
2010
2024
2024

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 34 publications
(18 citation statements)
references
References 27 publications
0
18
0
Order By: Relevance
“…However, successful retreatment of patients in whom the initial GK treatment fails is also feasible [9], as was illustrated in this case with the second GKRS. Overall, repeat GKRS has been shown to provide significant pain relief in more than 2/3 of patients [10, 11], with some studies showing similar [12, 13] and others showing better [11] overall facial-pain outcomes than primary radiosurgery. Studies have also demonstrated that lack of a prior neurosurgical procedure was predictive of better pain control [14, 15].…”
Section: Discussionmentioning
confidence: 99%
“…However, successful retreatment of patients in whom the initial GK treatment fails is also feasible [9], as was illustrated in this case with the second GKRS. Overall, repeat GKRS has been shown to provide significant pain relief in more than 2/3 of patients [10, 11], with some studies showing similar [12, 13] and others showing better [11] overall facial-pain outcomes than primary radiosurgery. Studies have also demonstrated that lack of a prior neurosurgical procedure was predictive of better pain control [14, 15].…”
Section: Discussionmentioning
confidence: 99%
“…Two studies published only with two year interval from single center was reduced to one vote (17,18). Partially duplicate studies including repeat GKS patients as a subgroup was also considered as a vote (25).…”
Section: Trigeminal Nerve Deficitsmentioning
confidence: 99%
“…Case reports with one or several cases were excluded and studies with at least 10 patients were included (42). Partially duplicate studies from the same GKS center were considered as single vote (17, 18,25,42).…”
Section: A N U S C R I P Tmentioning
confidence: 99%
See 1 more Smart Citation
“…As expected, similar results were found in the other study by Fountas et al [37]; however, no prior radiosurgical procedures were performed in the patient group with a history of prior procedures. Huang et al [38] conducted a study where 89 patients with idiopathic TN were treated with GKRS as an initial management approach, 20 of which underwent a subsequent GKRS procedure for facial pain recurrence. Following the initial radiosurgical procedure, 50 patients (56%) had an excellent response, 12 patients (13.5%) had a good response, and 7 patients (7.9%) had a fair response.…”
Section: Review Of Gamma Knife Radiosurgery For Trigeminal Neuralgiamentioning
confidence: 99%